Determinants of Dividend Payout Ratio in Non-Financial Companies Listed - Wafa Anggraeny; Robiyanto Robiyanto; Imanuel Madea Sakti (International Journal of Social Science and Business, 2020)
This study aims to analyze the effect of both internal and external factors that determine the dividend payout ratio of non-financial companies listed in the IDX High dividend 20 during the period of 2015-2019. The independent variables of the company's internal factors are return on assets, earnings per share, and debt to equity ratio. The independent variables of the company's external factors are interest rates and inflation. The control variable used in this study is firm size. There were 13 companies listed in IDX High Dividend 20 by using the purposive sampling method. Data analysis used panel data regression which was analyzed three times by grouping the dividend payout ratio, low dividend, and high dividend. The results showed that the return on assets had a significant negative effect on the combined dividend payout ratio with a probability value (0.0309) and high dividend with a probability value (0.0067) smaller than the significance level (5%), but had no significant effect on the low dividend with a probability value (0.3283) greater than the significance level (5%). Earnings per share has no significant effect on the combined dividend payout ratio with a probability value (0.4151), low dividend with a probability value (0.1164), and high dividend with a probability value (0.3835) greater than the significance level (5%). It can be concluded that return on assets earning per share, firm size, and debt to equity ratio have an effect on dividend payout ratio.